Female mice lacking cholecystokinin 1 receptors have compromised neurogenesis, and fewer dopaminergic cells in the olfactory bulb - Sui, Yi; Vermeulen, Rob; Hökfelt, Tomas; Horne, Malcolm K.; Stanic, Davor (Frontiers in Cellular Neuroscience, 2013)
Neurogenesis in the adult rodent brain is largely restricted to the subependymal zone (SVZ) of the lateral ventricle and subgranular zone (SGZ) of the dentate gyrus (DG). We examined whether cholecystokinin (CCK) through actions mediated by CCK1 receptors (CCK1R) is involved in regulating neurogenesis. Proliferating cells in the SVZ, measured by 5-bromo-2-deoxyuridine (BrdU) injected 2 hours prior to death or by immunoreactivity against Ki67, were reduced by 37% and 42%, respectively, in female (but not male) mice lacking CCK1Rs (CCK1R-/-) compared to wild-type (WT). Generation of neuroblasts in the SVZ and rostral migratory stream was also affected, since the number of doublecortin (DCX)-immunoreactive (ir) neuroblasts in these regions decreased by 29%. In the SGZ of female CCK1R-/- mice, BrdU-positive (+) and Ki67-ir cells were reduced by 38% and 56%, respectively, while DCX-ir neuroblasts were down 80%. Subsequently, the effect of reduced SVZ/SGZ proliferation on the generation and survival of mature adult-born cells in female CCK1R-/- mice was examined. In the OB granule cell layer (GCL), the number of neuronal nuclei (NeuN)-ir and calretinin-ir cells was stable compared to WT, and 42 days after BrdU injections, the number of BrdU+ cells co-expressing GABA- or NeuN-like immunoreactivity (LI) was similar. Compared to WT, the granule cell layer of the DG in female CCK1R-/- mice had a similar number of calbindin-ir cells and BrdU+ cells co-expressing calbindin-LI 42 days after BrdU injections. However, the OB glomerular layer (GL) of CCK1R-/- female mice had 11% fewer NeuN-ir cells, 23% less TH-ir cells, and a 38% and 29% reduction in BrdU+ cells that co-expressed TH-LI or GABA-LI, respectively. We conclude that CCK, via CCK1Rs, is involved in regulating the generation of proliferating cells and neuroblasts in the adult female mouse brain, and mechanisms are in place to maintain steady neuronal populations in the OB and DG when the rate of proliferation is altered.